The Amaranthaceae family in the flora of Donyztau - Kuanbay, Zh.I.; Admanova, G.B.; Abiev, S.A.; Kozhamzharova, L.S. (Fundamental and Experimental Biology, 2022)
The article discusses the distribution of the Amaranthaceae family of the Donyztau chunk in the Aktobe region. In the Donyztau flora, 25 genera have been registered, which combine 67 species. The Amaranthaceae family occupies the first place in the species of the Donyztau flora, making up 20 % of the entire flora. Taxonomic analysis showed that Salsola, Anabasis, Suaeda, Climacoptera, and Atriplex belong to the dominant genera in the family. The article provides a summary of the species of the family. An ecobiomorphological analysis of the species composition of the Amaranthaceae family depending on the substrate, was carried out. Analysis of the life forms is developed according to the classification of I.G. Serebryakov, ecological analysis — according to the classification of A.P. Shennikov. The analysis of life forms displayed the predominance of annual species. Ecological analysis has proved that the vast majority of species belong to xerophiles. Their share is 80 %. The article provides a synopsis of the species of the genus. The summary reflected the Latin-Kazakh names of species, life forms, ecological groups associated with the substrate, economic significance and area. Some species play an important role as an edifier.